An Unusual Phenomenon of Tourniquetinduced Hypertension in a Young Adult Male Undergoing Lower Limb Surgery under Subarachnoid Block: A Case Report - Mridul Madhav Panditrao; Sarita Swami; Rohan Thombare (Journal of Clinical and Diagnostic Research)
The employment of tourniquet to achieve bloodless surgical field is an essential step, especially in upper/lower extremity orthopaedic surgical procedures. However, tourniquet itself can lead to many possible problems, posing challenges to the anaesthesiologists. One such is exaggerated hypertensive response sometime after inflation of tourniquet, aptly termed as Tourniquet-induced Hypertension (TIH/T-HTN). It may not be evident in some patients, but if and once established, it becomes practically impossible to minimise/reverse it. This can be a nightmarish experience for the anaesthesiologist concerned. The authors hereby present one such case where, a young, healthy 25-year-old male posted for arthroscopy of right knee, who was administered subarachnoid block with dexmedetomidine as an adjuvant to bupivacaine. Within 35 to 40 minutes of inflating the torniquet, he developed severe hypertensive response, with blood pressures ranging from a Systolic Blood Pressure (SBP) of 190 to 210 mmHg and a Diastolic Blood Pressure (DBP) of 118 to 125 mmHg. It remained unresponsive to any form of treatment, including, the sedation with Inj. Midazolam or incremental doses of Inj. Labetalol. The hypertension persisted throughout the duration of surgery, while patient remained comfortably asleep. However, at the end of the surgical procedure, as soon as the tourniquet was deflated, the Blood Pressures (BPs), both SBP and DBP dropped to baseline values. Also, includes an in-depth review of the available literary evidence about this phenomenon and provided specific deductions and recommendations/remedial measures.